Supply Chain Optimization - Geunes, Joseph; Pardalos, Panos M.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2005)
Supply Chain Optimization captures the latest results in a segment of current research activity in supply chain management. This research area focuses on applying optimization techniques to supply chain management problems. The research papers that make up the volume provide a snapshot of state-of-the-art optimization methods within the field. This book presents rigorous modelling approaches for supply chain operations problems with a goal of improving supply chain performance (or the performance of some segment thereof). It contains high-quality works from leading researchers in the field whose expertise fits within this scope. The book provides a diverse blend of research topics and novel modelling and solution approaches for difficult classes of supply chain operations, planning, and design problems. Audience This book is intended for • researchers in supply chain management, applied operations research, and optimization; • industry practitioners in supply chain management with interests in operations management and operations research; • graduate students in supply chain management and optimization-related disciplines.
Information Centric Optimization of Inventories in Capacitated Supply Chains: Three Illustrative Examples -- An Analysis of Advance Booking Discount Programs Between Competing Retailers -- Third Party Logistics Planning with Routing and Inventory Costs -- Optimal Investment Strategies for Flexible Resources, Considering Pricing -- Multi-Channel Supply Chain Design in B2C Electronic Commerce -- Using Shapley Value to Allocate Savings in A Supply Chain -- Service Facility Location and Design with Pricing and Waiting-Time Considerations -- A Conceptual Framework for Robust Supply Chain Design Under Demand Uncertainty -- The Design of Production-Distribution Networks: A Mathematical Programming Approach -- Modeling & Solving Stochastic Programming Problems in Supply Chain Management Using Xpress-SP -- Dispatching Automated Guided Vehicles in a Container Terminal -- Hybrid MIP-CP Techniques to Solve a Multi-Machine Assignment and Scheduling Problem in Xpress-CP.
Keywords: Production management; Mathematical optimization; Operations research; Decision making; Applied mathematics; Engineering mathematics; Industrial procurement; Operations Management; Optimization; Operations Research/Decision Theory; Applications of Mathematics; Procurement